Principios de la gestión de las contrataciones de bienes del estado, acciones institucionales y personales, Municipalidad Provincial de Requena, año 2021 - Meléndez Celis, Keen Patrick (2024)
The objective was to determine the differences in the behavior of institutional and personal actions when implementing principles related to the contracting of goods in a provincial municipal institution, Requena; Type of descriptive comparative and quantitative research, with a sample of 10 workers, to whom a questionnaire was applied. The results are: institutional actions to implement these principles with transparent information have not received resources, 85.71%. For promotional campaigns, 71.43% point to no resources. In the development of internal rules to implement these principles, some resources have been allocated. Regarding the institutional actions to achieve capacities on these principles, they present better performance, some resources have received, 57.14% in freedom of competition, 42.86% in equal treatment, 57.14% in integrity. The highest occurred in transparency, 71.43%. Regarding personal actions, they have some results, 57.14% of them indicate that they have assumed an ethical culture; 85.71% said they sought to learn from people who know the subject. 71.43% have participated in many events on the subject. On the basis of the dominance of principles, 71.43% fall into freedom of competition as well as equal treatment. A lot of dominance, 71.43% in freedom of competition. No domain, 71.43% in technological validity and equity, 85.71% in environmental and social sustainability.